The Effect of Green Supply Chain Management on Energy and Economic Environment Conditions of Company Financial Performance - Pranoto Pranoto; Udin Ahidin; Ali Maddinsyah (International Journal of Supply Chain Management, 2020)
Abstract— This research intends to find out and further analyze the influence of the application of Green Supply Chain Management (GSCM) policy on energy and the condition of the Indonesian economy to the company's financial performance and its implication for the value of the company. The population of this study was mining and energy companies in the various sectors of the mining and energy subsection listed on the Indonesia Stock Exchange which numbered 13. This study estimated the factors that influence financial performance and their implication for firm value. The company's financial performance is measured by using return on assets (ROA). Factors that influence ROA used in this study: debt to asset ratio (DAR), debt to equity ratio (DER), energy policy ratio, institutional ownership, exchange rate, and interest rate. The research method used in this study is quantitative research using secondary data onto the period of 2010 - 2015. This study used a purposive sampling method of collecting data samples and companies that met the sampling criteria amounted to 12, while the data analysis method used was the data regression method. Based on the research results, the factors that influence financial performance significantly are the rupiah exchange rate, interest rates, DAR, and energy policy. Then the variables that affect the company's value significantly are ROA and the Rupiah exchange rate. Then Based on the R square value formed, the independent variable can explain the ups and downs of ROA of 53.28% and the rise and fall of the company's value of 48.09%.